EFFICACY OF PREEMPTIVE PREINCISIONAL USE OF KETAMINE ON POSTOPERATIVE PAIN RELIEF FOLLOWING APPENDECTOMY (Basrah Journal of Surgery, 2015)
Pain, which is often inadequately treated, accompanies the surgical procedures may persist long after tissue healing. Preemptive analgesia, involves the introduction of an analgesic regimen before the onset of noxious stimuli. Previous studies have suggested that ketamine, an N-methyl-D-aspartate (NMDA) receptor antagonist, provides a preemptive analgesic effect. In literature, its use is controversial; for this reason the aim of our research is to evaluate whether the preemptive use of ketamine decreases postoperative pain in patients undergoing appendectomy. In double-blind, randomized clinical trial, 100 patients underwent appendectomy for acute appendicitis were studied. Patients were randomly assigned into two groups. In the operating room, patients in the ketamine group received 0.5 mg/kg of ketamine IV 10 minutes before the surgical incision. In control group the same volume of normal saline was injected. Pain intensity was assessed at time 0 (the time of complete consciousness), 4, 12, 24 hours postoperatively using the visual analogue scale (VAS). One hundred patients (50 for both groups) were enrolled. For all the evaluated times, the VAS score was significantly lower (p value <0.05) in the ketamine group compared to the control group. There was a highly significant difference between the groups regarding the interval time of analgesic need. The total dose of tramadol in the first 24 hours was 2.42±0.70mg/kg in ketamine group and 3.86±0.35mg/kg in control group (p=0.009). The occurrence of nausea and vomiting in ketamine group was less than in control group. Three patients experienced brief nondisturbing hallucination in the recovery room in ketamine group. No other drug side effects in ketamine group were noticed. In conclusion, low dose of intravenously administered ketamine had a preemptive effect in reducing pain after appendectomy.